The Correlation of D- Dimer and Neutrophil Lymphocyte Ratio (NLR) Levels on COVID-19 Mortality - Nurhayatun, Evi; Ayu Safira, Meilani; Nurudhin, Arief (JURNAL INFO KESEHATAN, 2023)
Coronavirus disease 2019 (COVID-19) is a disease caused by a novel coronavirus or a new type of corona virus, namely severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). D-dimer and Neutrophil Lymphocyte Ratio are parameters that can be used as a predictor of mortality in COVID-19, so this study aims to determine the relationship between D-dimer levels and NLR with mortality in COVID-19 patients. The study used an analytic observational method with a cross sectional approach from medical record data at UNS Hospital. The population in this study were COVID-19 patients at UNS Hospital who had their D-dimer and NLR levels checked in the period November 2020-January 2021. The sample was taken using a simple random sampling technique. Bivariate data analysis with Spearman Rank Correlation Test. Obtained 72 samples. 46 male patients and 26 female patients with the highest age range of 40-59 years as many as 34 patients. Patients who experienced mortality as many as 24 people while the rest survived. Spearman's Rank test obtained p-values of D-dimer and neutrophil lymphocyte ratio (NLR) with mortality of COVID-19 patients 0.009 and <0.001, respectively. While the correlation coefficients for D-dimer and NLR on mortality were 0.308 and 0.515, respectively. There is a relationship between D-dimer and NLR levels with mortality in COVID-19 patients with a positive correlation.